Uso de actividades lúdicas innovadoras como estrategia metodológica para la enseñanza del idioma inglés dirigido a los estudiantes del séptimo año de educación general básica de la Unidad Educativa Fiscomisional “San Miguel” cantón San Miguel, provincia Bolívar, periodo 2017-2018 - Argüello Vargas, Mirian Raquel (2018)
The present work of degree is an investigation wich deals with teaching –learning work of the English Language in the students of Seventh Year of Basic General Education of the Educational Unit Fiscomisional SanMiguel, the way of working of the teacher, without awkening the interest in the students is the reason that motivated us to carry out this investigation. Thus, the need arises to work on a methodological proposal wich is of general interest in the institution as a contribution to the expansion of educational work, because through it, we propose the use of three innovative playful activities to be applied in order to capture the student’s attention and awaken their interest in learning this language so necessary worldwide, as a contribution to their exellent student development and future optimal professional development, since it is universal knowledge the need for students in addition to their mother tongue, , to expand their knowledge by learning the language spoken in most of the world. Based on this perspective, this work is proposed as a pedagogical tool to renew the teaching - learning process of the English language with the students of the Seventh Year of Basic General Education of the San Miguel Educational Unit, this will help us to reach a significant level of learning, wich is the purpose that the teacher has at the beginning of each school year. The skills obtained with this methodological proposal are: Domain of the use of the English-Spanish, Spanish-English dictionary. Practice the four language skills, Listening, Reading, Speaking and Writing to memorize and remember verbs, words and phrases. Analyzing the results obtained when applying our methodological proposal, we found that the objectives set at the beginning of this investigation, were achieved, affirming in this way the need to use innovative playful methodology to awaken the interest of the students when practicing teaching - learning and in this way make this work an atractive experience, for both the teacher and the student